Recombinant influenza A viruses as vaccine vectors. (3rd April 2019) - Gerlach, Thomas; Elbahesh, Husni; Saletti, Giulietta; Rimmelzwaan, Guus F.
ABSTRACT: Introduction : Various viruses, including poxviruses, adenoviruses and vesicular stomatitis virus, have been considered as vaccine vectors for the delivery of antigens of interest in the development of vaccines against newly emerging pathogens. Areas covered : Here, we review results that have been obtained with influenza A viruses (IAV) as vaccine vectors. With the advent of reverse genetics technology, IAV-based recombinant vaccine candidates have been constructed that induce protective immunity to a variety of different pathogens of interest, including West Nile virus, Plasmodium falciparum and respiratory syncytial virus. The various cloning strategies to produce effective and attenuated, safe to use IAV-based viral vectors are discussed. Expert commentary : It was concluded that IAV-based vector system has several advantages and holds promise for further development.